Integrated analysis of bulk and single-cell RNA sequencing reveals the interaction of PKP1 and tumor-infiltrating B cells and their therapeutic potential for nasopharyngeal carcinoma - Huang, Yu-Mei; Wang, Lin-Qian; Liu, Ying; Tang, Fa-Qing; Zhang, Wen-Ling (Frontiers in Genetics, 2022)
Immunotherapy is an individualized therapeutic strategy for nasopharyngeal carcinoma (NPC). However, few molecular targets are clinically satisfactory. This work aimed to integrate bulk and single-cell RNA sequencing data to identify novel biomarkers involved in NPC. We performed differentially expressed gene (DEG) analysis, Gene Ontology (GO) enrichment, Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analysis, and immune cell infiltration analysis prior to correlation analysis of the identified genes and immune cells and further assessed the prognostic effects of the biomarkers and immune cells in NPC. As a result, PKP1, a potential molecular biomarker associated with immune infiltration, and tumor-infiltrating lymphocyte-B cells (TIL-Bs) were identified as promising therapeutic targets for NPC. Importantly, immunohistochemistry (IHC) validated that PKP1 protein expression was mainly found in NPC cells rather than noncancerous cells. In addition, the tumor microenvironment (TME) of NPC was characterized by the infiltration of more dendritic cells (DCs) and γδT cells but fewer B cells. Our results suggest that the interaction of PKP1 and TIL-B cells is involved in NPC development. It is possible that TIL-B cells produce immunoglobulin G (IgG) to tumor antigens, such as PKP1, or viral antigens, including EBV and HPV, to execute antitumor ability through DC and T cells. In response, NPC cells express proteins such as PKP1 (absent in normal nasopharynx) to induce myeloid-derived suppressor cell (MDSC) expansion, which subsequently impairs the proliferation of B cells and results in B-cell death by generating iNOS and NOX2. In summary, our findings provide a potential therapeutic strategy for NPC by disrupting the interaction of PKP1 and TIL-Bs in the TME.